The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10336-016-1382-y
|View full text |Cite
|
Sign up to set email alerts
|

Parent-offspring interactions in a long-lived seabird, the Little Auk (Alle alle): begging and provisioning under simulated stress

Abstract: Long-lived seabirds are good models to study the mechanisms that mediate the parent-offspring interactions. Contrary to studies under natural conditions, experimental manipulations allow us to assess the birds' reactions in a short time period. We used the stress hormone corticosterone as an independent experimental factor to simulate the stress reaction, to examine changes in the behaviour of Little Auk chicks and parent birds. In the first experiment, we hypothesised that after enhancement of the corticoster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…An inhibition of trophallaxis with younger nurse bees under threatening conditions aligns with the phenomenon in which some species of birds decrease their parental provisioning to redirect energy towards self-maintenance in stressful conditions 32,33 . On the evolutionary scale, unpredictable and poor environments lead to parents paying less attention to chicks’ begging and instead using cues such as body size to determine provisioning 34 .…”
Section: Discussionsupporting
confidence: 59%
“…An inhibition of trophallaxis with younger nurse bees under threatening conditions aligns with the phenomenon in which some species of birds decrease their parental provisioning to redirect energy towards self-maintenance in stressful conditions 32,33 . On the evolutionary scale, unpredictable and poor environments lead to parents paying less attention to chicks’ begging and instead using cues such as body size to determine provisioning 34 .…”
Section: Discussionsupporting
confidence: 59%
“…Since the costs of foraging are considerable (Gabrielsen et al 1991;Konarzewski et al 1993), parent birds should also be resistant to chick begging, so potentially, the evolution of parent-offspring communication could be constrained. Nevertheless, Little Auk parents do communicate with their chicks acoustically (Kidawa et al 2017), and potentially in other ways, too. The contrasting expectation and results create an intriguing background for examining the issue of parent-offspring communication.…”
Section: Parental Carementioning
confidence: 99%
“…A study on little auk parents with experimentally increased flight costs during the chick-rearing period revealed that they are able to increase parental effort to some extent (Harding et al 2009). Also, it has been revealed that artificially increased chick-begging intensity (by the exogenous corticosterone administration) induced a higher feeding frequency by little auk parents (Kidawa et al 2017). An extension of parental effort, however, may affect parents' survival.…”
Section: Introductionmentioning
confidence: 99%